(untitled) (PANGEEA, 2025)
ABSTRACT. For a New and Better Understanding of Environmental Protection In the first part of the presentation the author resumes and summarizes the concept of the Vital Natural Atmospheric Calotte, first presented at the ELSEDIMA 2012 conference, as the limited space on planet Earth where people live freely, naturally, without any support. The essential parts of this space are air and earth. The paper then identifies and lists some of the potential and likely consequences upon human activities which can arise from adopting the calotte concept. Reference is made to the ownership of humans upon the planet’s environmental elements - earth, air, water - and upon the planet’s wildlife biodiversity, as well as to the need to change humans’ attitude towards the planet’s environment, including the calotte. The third part of the paper shows the connections between human senses and the physical fields of the planet, the influence of these fields upon human life and the planet’s biodiversity, although they are not directly perceived by humans. The author argues and presents the planetary geophysical fields as a whole, as the fourth environmenta element of the planet, which conditions life and the quality of life on planet Earth, together with air, earth and water as we understand them now. Key words: planetary environmental elements; geophysical fields.